Desenvolvimento de métodos analíticos e estudo de interferências para a determinação de elementos Terras Raras em sangue por ICP-MS - Druzian, Gabriel Toneto (2021)
In this work five analytical methods were investigated for rare earth elements determination (REE) in blood by inductively coupled plasma mass spectrometry (ICP-MS): i) Electrothermal vaporization and inductively coupled plasma mass spectrometry (ETV-ICP-MS), ii) conventional wet digestion in open system (CWD-OS), iii) conventional wet digestion in clossed system (CWD-CS), iv) microwaveassisted wet digestion using a single reaction chamber (MAWD-SRC) and v) microwave induced combustion (MIC). For CWD-OS, CWD-CS, MAWD-SRC and MIC, which used ultrassonic nebulization (USN), a systematic investigation of possible interferences for the determination of REE using this sample introduction system was carried out. The effect of Ca, Fe, K, Mg, Na, C (from citric acid, fructose and digested bovine liver) concentration were investigated, as well as the effect of the concentration of HNO3, HCl and aqua regia. In general, signal suppression effects for all REE from 50 mg L-1 of Na and K, 75 mg L-1 of Ca and 100 mg L-1 Mg and Fe were observed in this study. In evaluating the C effect (from citric acid and fructose), an increase in the signal intensity of REE was observed from 250 mg L-1. For the HNO3 and aqua regia concentration, signal suppression of REE was observed from 10 and 20%, respectively. On the other hand, no interferences were observed in the determination of REE in the range of 5 to 30% of HCl. Additionally, a study was carried out from two complete factorial designs (23) investigating the effect of the concomitant concentration of Fe, K and Na and of C, Na and K, respectively, in determination of REE by USN-ICP-MS. It was observed that the sum of Na and K concentrations (50 mg L-1) interfere in the determination of the REE. Furthermore, these suppression effects caused by Na and K compete with the signal intensity increase effects caused by the presence of C (from citric acid). The obtained results by microwaveassisted wet digestion (MAWD) were used as reference values for the developed analytical methods. Each analytical method was optimized as a function of experimental parameters, such as sample mass, temperature, time, concentration of digested solution, among others. The investigated analytical methods were applied to human blood samples (samples A, B and C), bovine and pig blood (sample D and E, respectively). In addition, liver samples of bovine and pig were used (sample F and G, respectively). from the same animals that provided samples D and E. Additionally, a bovine liver sample (sample H) was used for the interference experiments. Regarding to ETV-ICP-MS, regardless of the experimental conditions used, it was observed that this method was not suitable for the determination of REE in blood, possibly due to the difficulty of separating the REE from the metals (Fe, Na and K) that are part of the blood. It is important to highlight that the blood mass used in the CWDOS, CWD-CS, MAWD-SRC and MIC methods is dependent on he concentration of Na and K present in each sample, based on the interferences observed on the systematic study for REE determination by USN-ICP-MS. The CWD-OS method was not considered suitable for blood digestion because regardless of the digestion solution used, it was obtained digests with fat in suspension. On the other hand, the CWD-CS method was suitable for the digestion of 0.4 g of liquid blood using 5 mL of 3 mol L-1 HNO3 + 1 mL of 30%H2O2. In the MAWD-SRC method, it was possible to digest 2 g of blood using 6 mL of 1 mol L-1 HNO3 at 270 ºC for 15 min. The MIC allowed the digestion of 0.45 g of blood using 6 mL of aqua regia as an absorbing solution. In view of the developed sample preparation methods, it is important to emphasize that the choice for each one depends directly on the concentration of the interfering metals in each sample, the analytical frequency and the instrumentation available in each laboratory.